Cell Imaging by Spontaneous and Amplified Raman Spectroscopies - Giulia Rusciano; Gianluigi Zito; Giuseppe Pesce; Antonio Sasso (Journal of Spectroscopy)
Raman spectroscopy (RS) is a powerful, noninvasive optical technique able to detect vibrational modes of chemical bonds. The high chemical specificity due to its fingerprinting character and the minimal requests for sample preparation have rendered it nowadays very popular in the analysis of biosystems for diagnostic purposes. In this paper, we first discuss the main advantages of spontaneous RS by describing the study of a single protozoan (Acanthamoeba), which plays an important role in a severe ophthalmological disease (Acanthamoeba keratitis). Later on, we point out that the weak signals that originated from Raman scattering do not allow probing optically thin samples, such as cellular membrane. Experimental approaches able to overcome this drawback are based on the use of metallic nanostructures, which lead to a huge amplification of the Raman yields thanks to the excitation of localized surface plasmon resonances. Surface-enhanced Raman scattering (SERS) and tip-enhanced Raman scattering (TERS) are examples of such innovative techniques, in which metallic nanostructures are assembled on a flat surface or on the tip of a scanning probe microscope, respectively. Herein, we provide a couple of examples (red blood cells and bacterial spores) aimed at studying cell membranes with these techniques.